2020
DOI: 10.1186/s42494-020-00016-y
|View full text |Cite
|
Sign up to set email alerts
|

The first-line management of psychogenic non-epileptic seizures (PNES) in adults in the emergency: a practical approach

Abstract: Distinguishing non-epileptic events, especially psychogenic non-epileptic seizures (PNES), from epileptic seizures (ES) constitutes a diagnostic challenge. Misdiagnoses are frequent, especially when video-EEG recording, the gold-standard for PNES confirmation, cannot be completed. The issue is further complicated in cases of combined PNES with ES. In emergency units, a misdiagnosis can lead to extreme antiepileptic drug escalade, unnecessary resuscitation measures (intubation, catheterization, etc.), as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Para Toffa et al (2020), "Independentemente do nível de certeza no diagnóstico da CPNE, é importante posteriormente encaminhar o paciente para acompanhamento epiléptico e neuropsiquiátrico." De fato, o encaminhamento à especialistas facilita a descoberta e promove com mais facilidade a investigação de epilepsia associada, a fim de tratar o quanto antes.…”
Section: Formas De Tratamentos Para Portadores De Crise Psicogênica N...unclassified
“…Para Toffa et al (2020), "Independentemente do nível de certeza no diagnóstico da CPNE, é importante posteriormente encaminhar o paciente para acompanhamento epiléptico e neuropsiquiátrico." De fato, o encaminhamento à especialistas facilita a descoberta e promove com mais facilidade a investigação de epilepsia associada, a fim de tratar o quanto antes.…”
Section: Formas De Tratamentos Para Portadores De Crise Psicogênica N...unclassified
“…traumatic experiences in the past, personality traits, relationships with relatives and frequent complaints about somatic symptom disorders. Studies have shown that over 82% of patients experienced trauma in their childhood, and from 40% to over 84% of patients were victims of sexual violence [9,10]. During the interview, over 44% of patients report craniocerebral trauma [11].…”
Section: (1):35-41)mentioning
confidence: 99%
“…The most crucial factors include traumatic experiences during childhood (violence, sexual abuse, emotional neglect, loss of a loved one), personality disorders (borderline personality), head injuries, benefits resulting from taking the role of a sick person (compassion, exemption from social roles, financial gratification). When confronted with stressful situations, patients with PNES subconsciously integrate an epileptic seizure [8,10]. This way they learn that an epileptic seizure protects Differentiating between nonepileptic and epileptic seizures [3,4,8,9,10,12,13,14,16,17,21,26] Observation/Symptoms The following are useful in the treatment of PNES [7,16,17]:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations